Basic Concepts of Group Counseling: An Intervention Services - Habsy, Bakhrudin All; Zain, Hilda Hanuf Hamida; Masruroh, Hanim; Mukti, Farrel Alvydi (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study is based on the importance of the conceptions and propositions of group counseling as an integrated part of the overall comprehensive guidance and counseling program in schools. The target of group counseling activities is individual counselees by utilizing the group atmosphere as a way of treatment and a means of remedial and self-development.  This research uses qualitative methods, with the type of literature study as an attempt to interpret a text in a scientific way in search of rational meaning. The results of the research, resulting in a group counseling framework include: (a) The meaning of group counseling, (b) The purpose of group counseling, (c) The benefits of group counseling, (d) The principles in group counseling, (e) The conceptual framework of group counseling The focus of this research is how is the basic concept of group counseling